Evaluation of Electronic MedicalRecords (SIMPUS) at ABC XYZ Community Health Center Using the EUCS Method - Berkah Putri Lefesi (SMART : Jurnal Teknologi Informasi dan Komputer, 2025)
The  Health  Center  Information  System  (SIMPUS)  as  an  electronic  medical record platform is a key instrument in realizing the digitalization of primary health  services  in  Indonesia.  However,  implementation   without  proper evaluation risks resulting in systems that do not meet user needs. This study evaluates user satisfaction with the electronic medical records (SIMPUS) at Puskesmas   ABC,   XYZ   Regency,   YYY   Province   using   the   End   User Computing Satisfaction (EUCS) method. The research employs a descriptive quantitative approach  with a cross-sectional design. Respondents consisted of  52  health   workers   who  actively  use  SIMPUS,  selected  using  total sampling.  Data  were  collected  through  a  structured  questionnaire  adapted from  the  EUCS  instrument  covering  five  dimensions:  Content,  Accuracy, Format,  Ease  of  Use,  and  Timeliness.  Validity  and  reliability  tests  were conducted  before  data  collection.  Data  analysis  used  descriptive  statistics and  gap  analysis  between  expectations  and  perceptions.  Results  show  an overall  user  satisfaction  index  of  72.6%  (Good  category).  The  highest satisfaction was found in the Accuracy dimension (75.8%) and the lowest in the  Ease  of  Use  dimension  (67.4%).  Gap  analysis  reveals  the  largest negative gap in Ease of Use (gap score: −0.74), indicating that system ease of use is the most critical aspect requiring improvement. The novelty of this research  lies  in  the  application  of  gap  analysis  between  user  expectations and  actualperceptions  as  an  enrichment  of  the  standard  EUCS  method, providing    deeper    diagnostic    information    for    system    improvement recommendations  that  are  more  targeted  and  actionable  specifically  for SIMPUS in the Puskesmas context.